2006
DOI: 10.1016/j.envpol.2005.04.038
|View full text |Cite
|
Sign up to set email alerts
|

Tissues and hair residues and histopathology in wild rats (Rattus rattus L.) and Algerian mice (Mus spretus Lataste) from an abandoned mine area (Southeast Portugal)

Abstract: Data gathered in this study suggested the exposure of rats and Algerian mice, living in an abandoned mining area, to a mixture of heavy metals. Although similar histopathological features were recorded in the liver and spleen of both species, the Algerian mouse has proved to be the strongest bioaccumulator species. Hair was considered to be a good biological material to monitor environmental contamination of Cr in rats. Significant positive associations were found between the levels of this element in hair/kid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(34 citation statements)
references
References 51 publications
2
31
0
1
Order By: Relevance
“…In the liver and kidney of mice from the volcanic active area, the levels of those elements were so high that in the case of Pb they were very close to the ones found in bank voles from an abandoned lead mine in UK, and in mice and rats from a sulfur mine in Portugal mainland. In the case of Cd and Zn, levels found in the liver and kidney were 10-30 times and 2-6 times, respectively, higher to those of rodents from the abandoned mines mentioned before (Milton et al 2003; Viegas-Crespo et al Pereira et al 2006). The very high levels of Al, Cd, Pb, and Zn in mice from Furnas may result from the ingestion of food or soil rich in those metals but also from the inhalation of volcanic gases and aerosols that transport those elements (Durand and Grattan 1999;Ferreira and Oskarsson 1999;Durand et al 2004), as confirmed by the high levels found in the lung.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the liver and kidney of mice from the volcanic active area, the levels of those elements were so high that in the case of Pb they were very close to the ones found in bank voles from an abandoned lead mine in UK, and in mice and rats from a sulfur mine in Portugal mainland. In the case of Cd and Zn, levels found in the liver and kidney were 10-30 times and 2-6 times, respectively, higher to those of rodents from the abandoned mines mentioned before (Milton et al 2003; Viegas-Crespo et al Pereira et al 2006). The very high levels of Al, Cd, Pb, and Zn in mice from Furnas may result from the ingestion of food or soil rich in those metals but also from the inhalation of volcanic gases and aerosols that transport those elements (Durand and Grattan 1999;Ferreira and Oskarsson 1999;Durand et al 2004), as confirmed by the high levels found in the lung.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins are involved in the homeostasis and storage of copper and zinc, and play a protective role against the toxic effects of heavy metals, making them inactive and promoting their excretion (Kägi and Kojima 1987;Kägi and Schaffer 1988;Roesijadi 1994;Nordberg 1998;Binz and Kägi 1999). Therefore, cellular and tissue injuries, apoptosis and metallothionein expression may eventually be considered important biomarkers of the effects induced by chronic exposure to metals in natural conditions (Wlostowski et al 2000;Amaral and Rodrigues 2005;Amaral et al 2006b;Pereira et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…В последние годы в физиологических исследованиях в качестве неинвазивного метода оценки элемент-ного статуса применяется определение содержания химических элементов в волосах человека (Ревич, 1996;Скальный и др., 2012;Луговая, Максимов, 2012;Мирошников и др., 2012;Momcilovic et al, 2014) и шерсти у животных (крысы) (Скальный и др., 1990;Pereira et al, 2006;Lesage et al, 2010). Например, для определения элементного статуса организма животных (КРС − крупный рогатый скот) в качестве тест-объекта С.П.…”
Section: Introductionunclassified
“…Accumulation of heavy metals in parenchymatous organs of animals living in contaminated environment was described in detail in the literature. These studies reveal that heavy metals mainly accumulate in the liver (Plaa and Hewitt 1998;Garipay et al 2003;Pereira et al 2006;Stoltenberg et al 2003;Sween 2007).…”
mentioning
confidence: 99%